Формула решения квадратного уравнения!
ax^2+bx+c=0
x1=(-b+кор.кв.( b^2-4ac))/2a
x2=(-b-кор.кв.( b^2-4ac))/2a
где:
^2- значит в квадрате!
кор.кв.( b^2-4ac) - корень квадратный из выражения (b в квадрате -4*a*c)
1)5x^2-7x+2=0
x1=(7+кор.кв(49-40))/10=(7+3)/10= 1
х2=(7-кор.кв(49-40))/10=(7-3)/10= 0,4
2)3x^2+5x-2=0
x1=(-5+кор.кв.(25-24))/6=(-5+1)/6=-4/6= -2/3
x2=(-5-кор.кв.(25-24))/6=(-5-1)/6=-6/6= -1
3)2x^2-7x+3=0
x1=(7+кор.кв.(49-24))/4=(7+5)/4=12/4= 3
x2=(7-кор.кв.(49-24))/4=(7-5)/4=2/4= 1/2
4)3x^2+2x-5=0
x1=(-2+кор.кв(4+60))/6=(-2+8)/6= 1
x2=(-2-кор.кв(4+60))/6=(-2-8)/6=-10/6= -1(2/3)
5)5x^2-3x-2=0
x1=(3+кор.кв.(9+40))/10=(3+7)/10=10/10= 1
x2=(3-кор.кв.(9+40))/10=(3-7)/10=-4/10= -0,4
1) 5t(t-5)+2=2+5t
5t^2 - 25t + 2 - 2 - 5t = 0
5t^2 - 30t = 0
5t(t - 6) = 0
t1 = 0, t2 = 6
2)1-6(x2-x-1)=7
1- 6x^2 + 6x +6 -7 = 0
- 6x^2 + 6x = 0
-6x (x - 1) = 0
x1 = 0, x2 = 1
3)u-2(u2+u-1)=2
u- 2u^2 - 2u + 2 - 2 = 0
- 2u^2 - u = 0
-u (2u + 1) = 0
u1 = 0, u2 = -0.5
4)5x2-2x(x-3)=0
5x^2 - 2x^2 +6x = 0
3x^2 +6x = 0
3x (x + 2) =
x1 = 0, x2 = -2